2021
DOI: 10.1186/s12903-021-01957-7
|View full text |Cite
|
Sign up to set email alerts
|

Farsi version of the CLEFT-Q: translation, cultural adaptation process and reliability

Abstract: Background The purpose of this study was the translation and cultural adaptation of the CLEFT-Q to Farsi and evaluating the reliability of it. Methods The English version of the CLEFT-Q was translated to Farsi following the guidelines set forth by the International Society for Pharmacoeconomics and Outcomes Research (ISPOR). To calculate the reliability, 50 participants filled out the Farsi version of the questionnaire twice at 2-week intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…9 Having been translated into several languages, CLEFT-Q enables comparison between patients from different countries with various native languages. 20,21 This represents a significant development in facilitating international research collaboration on this relatively small patient group. Only a few word changes were required during the translation process of CLEFT-Q into Finnish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Having been translated into several languages, CLEFT-Q enables comparison between patients from different countries with various native languages. 20,21 This represents a significant development in facilitating international research collaboration on this relatively small patient group. Only a few word changes were required during the translation process of CLEFT-Q into Finnish.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire has been psychometrically validated with 2434 patients from 12 countries and has since been translated into several languages. 20 22 It has also been shown to be psychometrically valid when used on children and young adults with a range of other facial conditions. 23 The aim of this study was to produce and linguistically validate a Finnish version of the CLEFT-Q questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…CLEFT-Q continues to undergo translation and validation to other languages worldwide [63][64][65][66]. Multiple studies have demonstrated the validity and utility of CLEFT-Q [67] and the ICHOM standard set to the extent that, at this point, research is moving beyond content validity and focusing on the feasibility of implementation and verifying scales for their utility in clinically significant decision making.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…Institutional support and financial resources are vital to effective adoption and implementation, which can be a Outcomes Measurement (ICHOM) has also produced a standard set of standardized outcome measures [62] that is also commonly used by cleft teams for the comprehensive appraisal of cleft care (see Figure 2). CLEFT-Q continues to undergo translation and validation to other languages worldwide [63][64][65][66]. Multiple studies have demonstrated the validity and utility of CLEFT-Q [67] and the ICHOM standard set to the extent that, at this point, research is moving beyond content validity and focusing on the feasibility of implementation and verifying scales for their utility in clinically significant decision making.…”
Section: Outcome Measurementsmentioning
confidence: 99%